2017
DOI: 10.1111/exd.13396
|View full text |Cite
|
Sign up to set email alerts
|

The Sox2: GFP+/− knock‐in mouse model does not faithfully recapitulate Sox2 expression in skin

Abstract: Hair follicle heterogeneity may be regulated by distinct dermal papillae (DP) that represent mesenchymal lineages, which can be defined by Sox2 expression. However, it was recently shown that GFP expression in the Sox2: GFP+/− mouse model occurs in the DPs of all hair follicle types, challenging the idea that hair follicle heterogeneity can be defined by DP heterogeneity. Here, we investigated whether the knock-in mouse model faithfully expresses GFP when compared to endogenous Sox2 expression. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Secondly, we find abrupt changes in 3'UTR to CDS ratios in closely apposed but morphologically distinct tissues, such as Sox2 and Myc in the whisker dermal papillae and a number of genes in Ki67+ vs Ki67-cells in the hair follicle. Sox2 is critical in DP development [26,41] and shows equal 3'UTR to CDS in DP cells, whereas Myc, known for its role in proliferation, shows high 3'UTR. Interestingly, DP cells serve as a reservoir of stem cells (IPSC cells derive from the DP [42][43][44]; the high Myc 3'UTRlow CDS in these cells may allow them to maintain a non-proliferative, quiescent stem cell state.…”
Section: Stem Cell Biologymentioning
confidence: 99%
“…Secondly, we find abrupt changes in 3'UTR to CDS ratios in closely apposed but morphologically distinct tissues, such as Sox2 and Myc in the whisker dermal papillae and a number of genes in Ki67+ vs Ki67-cells in the hair follicle. Sox2 is critical in DP development [26,41] and shows equal 3'UTR to CDS in DP cells, whereas Myc, known for its role in proliferation, shows high 3'UTR. Interestingly, DP cells serve as a reservoir of stem cells (IPSC cells derive from the DP [42][43][44]; the high Myc 3'UTRlow CDS in these cells may allow them to maintain a non-proliferative, quiescent stem cell state.…”
Section: Stem Cell Biologymentioning
confidence: 99%
“…The skin wound specimens were fixed in 4% PFA for 12 hours at 4 o C and then prepared for histological processing according to [31]. Briefly, tissue samples were incubated in 30% sucrose for 24 hours, embedded in OCT, snap-frozen and cryosectioned (50-μm-thick sections).…”
Section: Methodsmentioning
confidence: 99%
“…While it was shown that the GFP+tdT+ population was well enriched in signature DP markers, the tdT+ single population could be attributed to the third-wave Zigzag hairs or DS cells, which are GFPÀ, and the small percentage of GFP+ single population may be the small population in the dermis that expresses Sox2, for instance the Schwann cells (Roberts et al, 2017;Torres-Mejı ´a et al, 2020). Also, even though Sox2 GFP knockin expression has been used by several groups to identify DP cells during morphogenesis and hair cycle, a recent publication has pointed out that these reporter mice do not faithfully report Sox2 endogenous protein levels in the skin, as they have an aberrant expression in the infundibulum and in the DP of HFs (Salz and Driskell, 2017).…”
Section: Limitations Of the Studymentioning
confidence: 99%